INTEREST IN PRODUCTIVE WAQF: HOW EFFECTIVE IS PROMOTION AND RELIGIOSITY? - Muhammad Resha Satyawicaksana; Abdul Razak Munir; Mursalim Nohong (Accounting Profession Journal (APAJI), 2023)
The aim of this research is to analyze the extent of the effectiveness of promotion and religiosity on interest in conducting productive waqf. This research is important to understand the factors influencing interest in productive waqf in Makassar City. The research results show that although partial religiosity did not exert a significant influence on the interest of productive endowments in Makassar City, it did suggest that other variables, such as promotion, interact and impact each other. Under these circumstances, religiosity may not be strong enough as the sole factor to encourage interest in productive endowments. However, when these two factors are combined with effective promotional efforts, they together increase awareness and understanding of productive endowments, as well as increase religious and social encouragement to participate. This suggests that in the context of Makassar, a combination of social, religious, and promotional information factors may be sufficient to drive interest.